An assessment of high school students' opinions on the use of methods and techniques in English classes - Gomleksiz, Mehmet Nuri (Elsevier Science Bv, 2014)
The purpose of this study is to explore students' opinions on the use of methods and techniques at English classes in a Turkish high school context. Data for the study were collected through a 23-item, five-point Likert scale from a total of 798 students at high schools in Elazig city, Turkey. The independent groups t-test and one way ANOVA were used to analyze the data. Statistically significant differences were observed in the gender, school type and grade level of the students. Male students considered methods and techniques more effective than female students did. They also found communication at English classes more sufficient and effective than females did. Findings revealed that female students were not satisfied with what the teachers used as teaching methods and techniques in English classrooms. Besides, statistically significant differences were observed among students' opinions in terms of grade level and school type variables. Additionally, some useful implications are discussed based on the research findings to construct and conduct English classes effectively. (C) 2013 The Authors. Published by Elsevier Ltd.
2nd World Conference on Design, Arts and Education (DAE) -- MAY 09-12, 2013 -- Ion Mincu Univ Architecture & Urbanism, Fac Architectural, Bucharest, ROMANIA
Keywords: Learning English; English language teaching; high school; high school student; teaching methods